2007
DOI: 10.1590/s1676-26492007000400008
|View full text |Cite
|
Sign up to set email alerts
|

Late side-effects of valproate and lamotrigine

Abstract: Lamotrigine (LTG) is a generally well-tolerated antiepileptic drug with broad-spectrum efficacy in several forms of partial and generalized epilepsy. Adverse effects of lamotrigine are usually associated with introduction and titration. This risk increases in children and in the co-medication with valproate. Herein, we report four patients with late adverse-effects, under the co-medication valproate and LTG, not related to drug introduction or titration. This study demonstrates that late side-effects without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Lamotrigine-induced rashes are usually divided into ‘benign’ and ‘serious’, with representative data provided by Calabrese et al 1 quantifying rates of 8.3% and 0% respectively in one sample and 13.1% and 0.1% in another. While there have been case reports 2 of late onset of side-effects, they have more been in the nature of neurological symptoms rather than rashes. I am not aware of any previous journal report of such a late-onset serious side-effect, although there are anecdotal reports on the internet.…”
Section: Discussionmentioning
confidence: 99%
“…Lamotrigine-induced rashes are usually divided into ‘benign’ and ‘serious’, with representative data provided by Calabrese et al 1 quantifying rates of 8.3% and 0% respectively in one sample and 13.1% and 0.1% in another. While there have been case reports 2 of late onset of side-effects, they have more been in the nature of neurological symptoms rather than rashes. I am not aware of any previous journal report of such a late-onset serious side-effect, although there are anecdotal reports on the internet.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that in patients with bipolar disorder after 12-week of lamotrigine monotherapy the volume of the cerebellum decreased (Bauer et al 2018). Cerebellar signs and symptoms, like ataxia, nystagmus, vertigo, as LTG side-effects were also noted in epilepsy patients (Moreira et al 2007;Thome-Souza et al 2012). These findings raise the possibility that lamotrigine-induced tremor might be a result of cerebellar dysfunction.…”
Section: Introductionmentioning
confidence: 90%
“…Various cerebellar symptoms, like nystagmus, ataxia, vertigo and tremor were reported as side effects of chronic co-medication of VPA and LTG at stable doses. Although serum levels were not provided, it might be hypothesized that these cerebellar signs were related to toxicity which ceased after 25-50 mg dose reduction of LTG (Moreira et al 2007). It was demonstrated that glutamate is necessary for oligodendrocyte proliferation and differentiation in the developing cerebellum (Yuan et al 1998).…”
Section: Recording Positionmentioning
confidence: 99%